2012
DOI: 10.1021/jp301000c
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Pulse Radiolysis of Nanoconfined Water

Abstract: The radiation chemistry of water in 1 and 57 nm pore diameter controlled pore glass is studied using nanosecond pulse radiolysis and compared to that of the bulk. The absorption spectrum of the solvated electron shows little dependence on the pore size suggesting that they solvate within the pore. It is shown that the reaction rate of the solvated electron increases dramatically with decreasing pore size, going from 6.8 × 10 6 s −1 in the bulk to 34.7 × 10 6 s −1 in a 1 nm pore. The initial yield (at 20 ns) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Furthermore, these authors were only able to determine that the hydrated electrons resided <1 nm from the interface. Because 1 nm is roughly three water molecular diameters, this means that the SHG experiment could effectively be probing hydrated electrons in the bulk. It is also worth noting that pulse-radiolysis experiments that produced hydrated electrons in water that was confined in 1 nm diameter silica pore glasses found that the confined electrons retain their bulk absorption spectrum, consistent with the idea that electrons need to be closer than 0.5 nm to a surface if non-bulk-like interfacial properties are to be detected …”
mentioning
confidence: 77%
“…Furthermore, these authors were only able to determine that the hydrated electrons resided <1 nm from the interface. Because 1 nm is roughly three water molecular diameters, this means that the SHG experiment could effectively be probing hydrated electrons in the bulk. It is also worth noting that pulse-radiolysis experiments that produced hydrated electrons in water that was confined in 1 nm diameter silica pore glasses found that the confined electrons retain their bulk absorption spectrum, consistent with the idea that electrons need to be closer than 0.5 nm to a surface if non-bulk-like interfacial properties are to be detected …”
mentioning
confidence: 77%
“…The reaction proceeds so efficiently that the radiolysis can be conducted at room temperature and ambient pressure. 29 Essentially, the species of and with low redox potentials - * serve as in-situ reductants, while the oxidative radical is scavenged by common alcohol additives, such as isopropanol and ethanol. Starting from this principle, Zhao and co-workers reported the synthesis of monodispersed Ag nanoparticles (NPs)/graphene nanocomposites using gamma radiation.…”
Section: Introductionmentioning
confidence: 99%
“…This has been associated with an unobservable H + H reaction in talc 36 . Furthermore, pulse radiolysis experiments performed in nanoporous silica have attributed most of the decay of solvated electron in the ns-µs timescale range to the e − + SiOH → SiO − + H reaction 74 . This suggests that the reaction with Mu, which is happening in the same timescale, occurs with H atoms and not with electrons, as electrons will react preferentially with MgOH groups in the present case.…”
Section: Resultsmentioning
confidence: 99%